Jet characteristics of CO2–O2 mixed injection using a dual-parameter oxygen lance nozzle for different smelting periods - Feng Chao (De Gruyter, 2021)
The jet performance of an oxygen lance nozzle influences the smelting rhythm, smelting index, and energy consumption of a converter. Due to the complexity of the process of converter smelting, the changing temperature and gas composition in the converter significantly impact the jet characteristics of the oxygen lance nozzle in the smelting process; however, research on the change law of jet characteristics in different smelting periods is limited. In this study, we used Ansys Fluent 17.0, which is commercially available fluid simulation software, to simulate the variation of jet characteristics of a mixed injection comprising 6% CO2 and 94% O2; the mixed injection was tested using a dual-parameter oxygen lance nozzle in the early, middle, and late stages of smelting. The results show that the increase of CO concentration and ambient temperature in the converter lead to a decrease in the attenuation rate of jet velocity, improved independence of multiple jets, and an increase in the impact area of jets on the molten pool. Thus, when designing and employing oxygen lance nozzles, the influence of ambient temperature and furnace gas composition on jet characteristics must be considered.